Firm entry and exit during recessions - Joao Ayres; Gajendran Raveendranathan (Inter-American Development Bank (IDB), 2021)
We analyze shocks to productivity, collateral constraint (credit shock), firm operation, and labor disutility in a model of firm dynamics with entry and exit. Shocks to firm operation and labor disutility capture COVID-19 lockdowns. Compared to the productivity shock, the credit and the lockdown shocks generate larger changes in firm entry and exit. The credit shock accounts for lower entry, higher exit, and concentration of exit among young firms during the Great Recession. The lockdown shocks predict a large fall in entry and rise in exit followed by a sharp rebound. In both recessions, changes in entry and exit account for 10-20 percent of the fall in output and hours. Finally, we discuss how the modeling of potential entrants matters for the quantitative results.
Keywords: D21; D22; E24; E32; 330; Firm dynamics; Recession; COVID-19; General equilibrium model; Credit shock; Lockdown